Controlled atmosphere storage modulates the exocarp-color and mesocarp-softening synchronization in ´Hass´ avocado - Camila Arancibia-Guerra; Gerardo Núñez-Lillo; Nathalie Kuhn; Excequel Ponce; Alegría Carrasco-Pancorbo; Esther Carrera; Jorge Baños; David Campos; Bruno Defilippi; Reinaldo Campos-Vargas; Claudio Meneses; Romina Pedreschi (Postharvest Biology and Technology, 2026)

Control of pore geometry on the strength, elastic anisotropy and acoustic emission output of vesicular lavas from Nevados de Chillán, Chile - Fernanda Merchán; John Browning; Gloria Arancibia; David Healy; Valentina Mura; Camila Pineda; Michael J. Heap; Patrick Baud; Jorge E. Romero; Matias Clunes; Luis Felipe Orellana; Diego Morata (Bulletin of Volcanology, 2026)
The strength and stiffness of lavas, as well as their propensity to fracture and develop permeable flow networks, are all governed by microstructural heterogeneity. In vesicular andesitic–dacitic lavas from the Nevados de Chillán Volcanic Complex (NChVC) in Chile, we show that uniaxial compressive strength (UCS) and Young’s modulus (E) depend not only on connected porosity but also on the distribution, orientation, size and aspect ratio of pores. Pore fabrics were first quantified via 2D analyses (transparent sections and surface imaging) and 3D micro–computed tomography (micro-CT). Then, using cylinders with pores aligned parallel, perpendicular, and inclined to the loading direction, we performed UCS tests instrumented with acoustic emission (AE) monitoring. Loading perpendicular to the pore major axis presents the lowest strength and stiffness and triggers AE output at low stress, whereas loading parallel to the pore major axis initiates damage at higher stress, attains relatively higher strength, and culminates in macroscopic failure with higher rates of AE concentrated near the peak stress. Mixed AE patterns are observed when loading at an inclined angle to the pore major axis. These observations are consistent with the theory of microcrack nucleation and propagation controlled by stress concentration around elliptical pores. While porosity exerts a first-order control on the overall magnitude of strength and stiffness, we conclude that pore alignment, aspect ratio and directional variability fundamentally modulate failure style, damage evolution, and rock mechanical properties. Operationally, this framework anticipates preferential directions of weakness and damage evolution prior to failure, thereby supporting assessments of the mechanical stability of lava domes, levees, and scoria cones composed of high porosity materials.

Harvest maturity modulates the synchronization between exocarp color change and mesocarp softening in avocado cv. Hass: A multiomics perspective - Camila Arancibia-Guerra; Gerardo Núñez-Lillo; Ignacia Hernández; Excequel Ponce; Nathalie Kuhn; Alegría Carrasco-Pancorbo; Lucía Olmo-García; Esther Carrera; Jorge Baños; David Campos; Bruno Defilippi; Reinaldo Campos-Vargas; et al. (Postharvest Biology and Technology, 2025)

Heterogeneous distribution of surface hydrothermal alteration in the Nevados de Chillán Fractured Geothermal System, Southern Andes - Camila López-Contreras; Gloria Arancibia; Valentina Mura; Santiago Maza; Diego Morata; Philippe Robidoux; John Browning; David Healy; John Singleton (Geothermics, 2025)

Structural control on the Southern Andean Nevados de Chillán geothermal system - Valentina Mura; Gloria Arancibia; John Browning; David Healy; Camila López-Contreras; Diego Morata; Santiago Maza; Carlos Cardona (Journal of Structural Geology, 2025)

Urbanization's hidden influence: Linking landscape alterations and feather coloration with pigeon's cholesterol levels - Javiera Arcila; Isaac Peña-Villalobos; Catalina B. Muñoz-Pacheco; Felipe Sanhueza-Cisterna; Daniela Galdames; David Arancibia-Altamirano; Fabiola A. Otárola; Diego Landaeta; Francisco del Basto; Carolina Cárdenas Aroca; Tomás Jiménez; Pablo Sabat; et al. (Environmental Research, 2025)

Deciphering the behind blackspot exocarp disorder in avocado cv. Hass through a hormonal, transcriptional and metabolic integration approach - Gerardo Núñez-Lillo; Ignacia Hernández; Patricio Olmedo; Excequel Ponce; Camila Arancibia-Guerra; Laura Sepulveda; Alegría Carrasco-Pancorbo; María Gemma Beiro-Valenzuela; Esther Carrera; Jorge Baños; David Campos; Claudio Meneses; et al. (Postharvest Biology and Technology, 2024)

Multi-million-year magmatic and hydrothermal activity is key to the formation of supergiant to behemothian porphyry copper deposits - Adrianna Luiza Virmond; Jörn-Frederik Wotzlaw; Rodrigo Rojas-Arancibia; David Selby; Cyril Chelle-Michou (Contributions to Mineralogy and Petrology, 2024)
Understanding the primary controls on mineral deposit formation and size is essential for sourcing the metals required by our ever-growing economy. The tonnage of porphyry copper deposits ranges five orders of magnitude but the key mechanisms and processes that modulate the size of these deposits remain enigmatic. Here, we investigate the behemothian deposits of the Chuquicamata Intrusive Complex (CIC) in northern Chile employing high-precision U–Pb and Re–Os geochronology. We resolve a complex long-lived magmatic-hydrothermal activity that lasted over 3.3 Myr. High-precision zircon petrochronology data indicate two distinct porphyry emplacement episodes, separated by 0.5 Myr, with the younger generation closely tied to the main intervals of hydrothermal mineralization. High-precision Re–Os molybdenite dates reveal a prolonged hydrothermal mineralization interval (> 2.5 Myr) that progressively migrated southwards within the CIC and continued after the end of the (apparent) magmatic activity. We show that the rate of copper precipitation varies little in nature (0.025–0.10 Mt/kyr) and is independent of the size of the deposit. Consistent with evidence from smaller deposits, our findings provide unprecedented evidence that copper endowment in porphyry copper deposits positively correlates with the timescales of magmatic and hydrothermal activity. Supergiant to behemothian deposits require multi-million-year magmatic-hydrothermal activity, linking the largest porphyry copper systems to a simple metric – the duration of magmatic-hydrothermal activity.

Non-indigenous species and their realized niche in tidepools along the South-East Pacific coast - David Jofré-Madariaga; Moisés A. Aguilera Moya; Catharina Alves-de-Souza; Rene Matías Arias; Lars Gutow; Ricardo Antonio Jeldres Polanco; Erasmo C. Macaya; Martín Munizaga Kappes; Leslie Nicole Ortiz Arancibia; Oscar Pino; Sabine Rech; Eva Rothäusler; et al. (Marine Environmental Research, 2024)

Prenatal caloric restriction adjusts the energy homeostasis and behavior in response to acute and chronic variations in food availability in adulthood - Isaac Peña-Villalobos; Fabiola A. Otarola; David Arancibia; Pablo Sabat; Verónica Palma (Journal of Comparative Physiology B, 2023)

How sensitive are catchment runoff estimates to on-farm storages under current and future climates? - David E. Robertson; Hongxing Zheng; Jorge L. Peña-Arancibia; Francis H.S. Chiew; Santosh Aryal; Martino Malerba; Nicholas Wright (Journal of Hydrology, 2023)

Characterising the regional growth of on-farm storages and their implications for water resources under a changing climate - Jorge L. Peña-Arancibia; Martino E. Malerba; Nicholas Wright; David E. Robertson (Journal of Hydrology, 2023)

A multiomics integrative analysis of color de-synchronization with softening of ‘Hass’ avocado fruit: A first insight into a complex physiological disorder - Gerardo Núñez-Lillo; Excequel Ponce; Camila Arancibia-Guerra; Sebastien Carpentier; Alegría Carrasco-Pancorbo; Lucía Olmo-García; Rosana Chirinos; David Campos; Reinaldo Campos-Vargas; Claudio Meneses; Romina Pedreschi (Food Chemistry, 2023)

Frequency and mitotic heritability of epimutations in Schistosoma mansoni - David Roquis; Anne Rognon; Cristian Chaparro; Jerome Boissier; Nathalie Arancibia; Celine Cosseau; Hugues Parrinello; Christoph Grunau (Molecular Ecology, 2016)
Schistosoma mansoni is a parasitic platyhelminth responsible for intestinal bilharzia. It has a complex life cycle, infecting a freshwater snail of the Biomphalaria genus, and then a mammalian host. Schistosoma mansoni adapts rapidly to new (allopatric) strains of its intermediate host. To study the importance of epimutations in this process, we infected sympatric and allopatric mollusc strains with parasite clones. Ch IP ‐Seq was carried out on four histone modifications (H3K4me3, H3K27me3, H3K27ac and H4K20me1) in parallel with genomewide DNA resequencing (i) on parasite larvae shed by the infected snails and (ii) on adult worms that had developed from the larvae. No change in single nucleotide polymorphisms and no mobilization of transposable elements were observed, but 58–105 copy number variations ( CNV s) within the parasite clones in different molluscs were detected. We also observed that the allopatric environment induces three types of chromatin structure changes: (i) host‐induced changes on larvae epigenomes in 51 regions of the genome that are independent of the parasites’ genetic background, (ii) spontaneous changes (not related to experimental condition or genotype of the parasite) at 64 locations and (iii) 64 chromatin structure differences dependent on the parasite genotype. Up to 45% of the spontaneous, but none of the host‐induced chromatin structure changes were transmitted to adults. In our model, the environment induces epigenetic changes at specific loci but only spontaneous epimutations are mitotically heritable and have therefore the potential to contribute to transgenerational inheritance. We also show that CNV s are the only source of genetic variation and occur at the same order of magnitude as epimutations.